Taking It Personally. Issue 2 (3rd April 2022) - Benjamin, Jessica
Abstract: The author reviews some of her personal and intellectual connections and experience in dialogue with Philip Bromberg, touching on a few ideas that have central importance for her as well as how he conveyed his own experience and feeling of what was important. She highlights how Bromberg influenced her and summarizes the way she understands her differences with him.